Book of unknown Americans - Henriquez, Cristina (Farmington Hills, Mich. Thorndike Press, 2014)
After their daughter Maribel suffers a near-fatal accident, the Riveras leave Mexico and come to America. But upon settling at Redwood Apartments, a two-story cinderblock complex just off a highway in Delaware, they discover that Maribel's recovery -- the piece of the American Dream on which they've pinned all their hopes -- will not be easy. Every task seems to confront them with language, racial, and cultural obstacles. At Redwood also lives Mayor Toro, a high school sophomore whose family arrived from Panama fifteen years ago. Mayor sees in Maribel something others do not: that beyond her lovely face, and beneath the damage she's sustained, is a gentle, funny, and wise spirit. But as the two grow closer, violence casts a shadow over all their futures in America.
102222
Keywords: Teenagers; Immigrants; Large type books; Delaware; Love stories; Large type books